Development of tight junctions de novo in the mouse early embryo: control of assembly of the tight junction-specific protein, ZO-1 (The Rockefeller University Press, 1989)
Tight junction development during trophectoderm biogenesis in the mouse preimplantation embryo has been examined using monoclonal antibodies recognizing the tight junction-specific peripheral membrane protein, ZO- 1. In immunoblots, mouse embryo ZO-1 had a molecular mass (225 kD) equivalent to that in mouse liver, was barely detectable in four-cell embryos although later stages exhibited increasing levels. ZO-1 was first detected immunocytochemically at the compacting eight-cell stage, coincident with or just after the expression of basolateral cell adhesion and apical microvillous polarity. Initially, ZO-1 was present as a series of spots along the boundary between free and apposed cell surfaces in intact embryos or cell couplets, but subsequently staining became more linear with blastocyst trophectoderm cells being bordered by a continuous ZO-1 belt. Inhibition of cell adhesion at the 8-cell stage delayed ZO-1 appearance and randomized its surface distribution in a reversible manner. Microfilament disruption, but not microtubule depolymerization, produced major disturbances in ZO-1 distribution. ZO- 1 assembly de novo appeared to be independent of proximate DNA and RNA synthesis but was inhibited substantially in the absence of protein synthesis during the eight-cell stage, a treatment that did not prevent intercellular adhesion and polarization. ZO-1 surface assembly, but not adhesion and polarization, was also perturbed when single eight-cells were combined with single four-cells. The results suggest that tight junction development in mouse embryos is a secondary event in epithelial biogenesis, being dependent upon cell adhesion and cytoskeletal activity for normal expression, and can be disrupted without disturbing the generation of a stably polarized phenotype.